2020
DOI: 10.3390/microorganisms8030333
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Anaerobic Digestion of Long Chain Fatty Acid by Adding Magnetite and Carbon Nanotubes

Abstract: This study investigated the impact of stimulating direct interspecies electron transfer (DIET), by supplementing nano-sized magnetite (nFe3O4, 0.5 g Fe/g VSS) and carbon nanotubes (CNT, 1 g/L), in anaerobic digestion of oleic acid (OA) at various concentrations (0.10–4.00 g chemical oxygen demand(COD)/L). Both supplementations could enhance CH4 production, and its beneficial impact increased with increased OA concentration. The biggest improvements of 114% and 165% compared to the control were achieved by nFe3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
1
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 41 publications
(18 citation statements)
references
References 68 publications
0
16
1
1
Order By: Relevance
“…This can justify the enhanced CH 4 productivity, as CBCM are supplemented ( Table 2). In case of IBCM, the electrical conductivity might have more remarkable impact than surface area [43,80]. Further study concluded that magnetite could play double role, i.e., (i) stimulating the up-regulated secretion of key enzymes that are involved in the substrate degradation and (ii) inducing the expression of DIET-related proteins [60].…”
Section: As a Tool For Diet Pathway Stimulationmentioning
confidence: 98%
See 2 more Smart Citations
“…This can justify the enhanced CH 4 productivity, as CBCM are supplemented ( Table 2). In case of IBCM, the electrical conductivity might have more remarkable impact than surface area [43,80]. Further study concluded that magnetite could play double role, i.e., (i) stimulating the up-regulated secretion of key enzymes that are involved in the substrate degradation and (ii) inducing the expression of DIET-related proteins [60].…”
Section: As a Tool For Diet Pathway Stimulationmentioning
confidence: 98%
“…Even, slight negative impact (−4%, compared to control) upon cumulative CH 4 production yield was observed by magnetite addition [62]. But, some reports showed that an increase in CH 4 yield can be also observed after CM supplementation [43,63]. DIET-stimulated digesters were also able to sustain against the harsh operational conditions, e.g., accumulation of sulfate [47] or ammonia [48] or phenol [29].…”
Section: As a Tool For Diet Pathway Stimulationmentioning
confidence: 98%
See 1 more Smart Citation
“…For each bottle, the substrate concentration and inoculum to substrate ratio were adjusted to be 2.0 g COD/L and 5.0 g volatile suspended solids (VSS)/g COD, respectively. Trace metals and nutrients were added to batch bottles [28,29]. Initial pH was adjusted to 7.5 ± 0.1 using KOH (2 N) and HCl (2 N) solutions, then purging was done for the serum bottles using 99.99% N 2 gas for 10 min for securing anaerobic condition.…”
Section: Pretreatment and Bmp Testmentioning
confidence: 99%
“…苯甲酸在共培养体系中被证实可作为DIET的底 物 [33] , 及导电磁铁介导的DIET产甲烷途径可加快矿稻 田土壤中互养代谢苯甲酸为甲烷 [29] , 暗示难降解复杂 有机物代谢可通过DIET产甲烷途径. 除苯甲酸之外, 导电材料介导的DIET产甲烷途径还可强化厌氧消化系 统中甘油 [41] 、油酸 [67] 、蔗糖 [40] 、胰蛋白胨 [90] 和苯 酚 [34] 等复杂有机物降解. Wang等人 […”
Section: 强化降解unclassified